Hexosylceramides as intrathecal markers of worsening disability in multiple sclerosis. (September 2015) - Checa, Antonio; Khademi, Mohsen; Sar, Daniel G; Haeggström, Jesper Z; Lundberg, Jon O; Piehl, Fredrik; Olsson, Tomas; Wheelock, Craig E
Background: Sphingolipids are important components of neurons and the myelin sheath whose levels are altered in multiple sclerosis (MS). Objectives: We aimed to determine if cerebrospinal fluid (CSF) sphingolipids can be used as markers of MS disease progression. Methods: Using liquid chromatography tandem mass spectrometry, we analysed sphingolipids in CSF from 134 individuals. The MS group included 65 patients divided into 41 relapsing–remitting MS (RRMS) and 24 progressive MS (ProgMS). In addition, a group of 13 early MS/clinically isolated syndrome (EarlyMS) and two control groups consisting of 38 individuals with other neurological diseases (OND) and 18 OND with signs of inflammation (iOND) were analysed. A follow-up study included 17 additional RRMS patients sampled at two time points 4.7±1.7 years apart. Results: Levels of sphingomyelin (SM)- and hexosylceramide (HexCer)-derived sphingolipids increased in the CSF of patients with MS independently of the fatty acid chain length in RRMS ( p <0.05). Levels of palmitic acid (16:0)-containing HexCer (HexCer16:0) increased significantly in ProgMS compared with the OND ( p <0.001), iOND ( p <0.05) and EarlyMS ( p <0.01) groups and correlated with Expanded Disability Status Scale in RRMS in both studies ( p =0.048; p =0.027). Conclusion: HexCer16:0 is a promising candidate marker of disease progression in MS, especially in RRMS.